2018
DOI: 10.1002/anie.201806780
|View full text |Cite
|
Sign up to set email alerts
|

Modular One‐Step Three‐Component Synthesis of Tetrahydroisoquinolines Using a Catellani Strategy

Abstract: Reported is a modular one-step three-component synthesis of tetrahydroisoquinolines using a Catellani strategy. This process exploits aziridines as the alkylating reagents, through palladium/norbornene cooperative catalysis, to enable a Catellani/Heck/aza-Michael addition cascade. This mild, chemoselective, and scalable protocol has broad substrate scope (43 examples, up to 90 % yield). The most striking feature of this protocol is the excellent regioselectivity and diastereoselectivity observed for 2-alkyl- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 70 publications
(13 reference statements)
0
25
0
Order By: Relevance
“…Hence, it was important to provide an ortho ‐substitution to ensure the necessary steric pulse. The proposition was also established by the study of Catellani and Dong [15b–d,k] . It was found that the β‐carbon elimination was facilitated by the presence of ortho ‐disubstitution.…”
Section: Methodsmentioning
confidence: 81%
“…Hence, it was important to provide an ortho ‐substitution to ensure the necessary steric pulse. The proposition was also established by the study of Catellani and Dong [15b–d,k] . It was found that the β‐carbon elimination was facilitated by the presence of ortho ‐disubstitution.…”
Section: Methodsmentioning
confidence: 81%
“…To diversify the scope of sulfonate scaffolds we tested several aryl iodides bearing ester ( 3 a and 3 b ) or nitro ( 3 c ) groups to provide the desired para ‐arylated compounds in good to excellent yields and selectivity. As mentioned earlier, 2,6‐disubstitution was unavoidable [12, 15b–d, k] to harness the desired palladium relay reactivity to achieve para ‐selective arylation. Therefore, we diversified the scope of arenes with respect to various 2,6‐disubstituted templates.…”
Section: Methodsmentioning
confidence: 98%
“…Zhou and co‐workers, in 2018, reported a powerful method for the synthesis of tetraidroisoquinolines 142 or 143 starting from simple aryl‐iodides 131 , aziridines 140 and electron‐poor olefins 141 . The protocol tolerates various substituents on both the aryl‐iodide, the aziridine as well as the olefin allowing to access to the tetraidroisoquinoline scaffold in good yields (Scheme ).…”
Section: Miscellaneousmentioning
confidence: 99%